Analysis of Factors Affecting Physicians' Job Satisfaction - Barliyan, Muh. Agus; Irianto, Torry Duet; Samino, Samino (Sarana Ilmu Indonesia (salnesia), 2025)
Dissatisfaction among physicians can lead to decreased productivity, thereby disrupting performance and patient care. This study aimed to identify several factors influencing physicians’ job satisfaction, namely income, job security, age, length of service, supervision, interpersonal relationships, workload, and motivation at Dr. H. Bob Bazar, SKM Regional General Hospital. This quantitative study used an analytical approach with a cross-sectional design. The study population consisted of 37 physicians from Dr. H. Bob Bazar, SKM Regional General Hospital in South Lampung. The sampling method was comprehensive sampling. Data were collected using a questionnaire. Data analysis was conducted using bivariate analysis (simple linear regression) and multivariate analysis (F-test). The results showed that income (p-value = 0,002), interpersonal relationships (p-value = 0,001), supervision (p-value = 0,010), workload (p = 0,000), and motivation (p = 0,000) had a significant effect on physicians’ job satisfaction. Job security (p-value = 0,051), age (p-value = 0,667), and length of service (p-value = 0,662) did not affect job satisfaction. The primary factor influencing physicians’ job satisfaction was workload, with a coefficient b = 0,347. The findings of this study reveal that income, interpersonal relationships, supervision, workload, and motivation influence physicians’ job satisfaction, whereas job security, age, and length of service do not. This study provides informative, analytical evidence to assist hospital administration in improving factors that affect physicians’ job satisfaction.